Topical proparacaine vs combined topical-intracameral lidocaine anesthesia in phacoemulsification surgery with preoperative counseling about intraoperative visual fear - Shakya, Kiran; Shakya, Sangita; Pokhrel, Ram Prasad; Malla, Om Krishna (Journal of Advanced Academic Research, 2018)
Background Phacoemulsication under topical anesthesia makes a quickest visual recovery and reduces surgical time. Topical anesthesia with supplementary intracameral lidocaine may reduce some pain during iris manipulation or iris diaphragm movement. Objective To study the anesthetic efficacy of topical 0.5% proparacaine hydrochloride versus combined topical - intracameral 1% lidocaine injection during phacoemulsification surgery. Method Total 80 patients divided into A and B, each group having 40 patients was enrolled in this study. Phacoemulsification was performed on group A under topical anesthesia with proparacaine hydrochloride 0.5% and on group B under combined topical - intracameral injection of 0.5cc 1% lidocaine. Preoperatively, all patients received counseling about the potential intraoperative visual fear. Each patient was shown visual analogue scale 10 minutes after completion of surgery and was recorded their pain score. Unco-operative patients and previous history of ocular trauma were excluded. Results According to visual analogue scale, on group A, 30% felt no pain, 50% felt mild pain and 20% felt tolerable moderate pain (level 4) and on group B, 80% felt no pain and 20% felt mild pain. The group A perceived pain higher than group B (P <0.001). Mean operation time was 10 minutes. Most of the patients in A and B groups had no eye movement (Group A: 88% and Group B: 95%). Conclusions The combined topical proparacaine - intracameral injection of lidocaine anesthesia is better than topical proparacaine during phacoemulsification ensuring patients and surgeons comfort. Preoperative counseling helps the patients to focus on operating microscope light during surgery.